A coesão sequencial em textos dissertativos de alunos do ensino médio - Vasques, Patricia Vergara Emmerich (2018)
The manifestation of thought is registered through the text production. Because of this necessity, this study has arisen from high school students´texts (3rd year) from E.E. João Ranalho in São Bernardo do Campo. As a Portuguese and Literature teacher in a public school, I have noticed that sometimes students could debate a certain topic, but when they had to write their conclusions, many difficulties used to appear. Also, I have noticed that the coherence of these texts was damaged not only because of problems in understanding the topic, but also because of the misuse of certain cohesive elements. Among 100 compositions, I have selected 16 for this research. The choice of these samples were based on problems with sequential cohesion, the target of this research, because I have noticed that students have always demonstrated many doubts in the use of these elements. At the end, there are some considerations about the conclusions of this study, whose goal is to make teachers work in a more effective way with their students.